Pemberdayaan Potensi Sumber Daya Alam Pada Desa Sampang Kecamatan Gedangsari Kabupaten Gunung Kidul - Ludvianto, Meganusa (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
In the implementation of the 79 Society 5.0 Real Work Lecture, Atma Jaya Yogyakarta University, the 79 Group created a work program related to empowering the potential of natural resources owned by Sampang Village. This work program aims to improve the local community's economy in the form of biogas and natural potentials in Sampang Village. This type of research was conducted based on direct observation by the group following health protocols and supported from Google sources. The data used in this study are primary data in the form of observations and searches via Google, while secondary data is in the form of journals and searches via Google or the internet. This data source was collected and analyzed qualitatively in Microsoft Word, then understood and assembled the storyline through existing data and collected through Whatsapp Group and Meet Microsoft Teams. Based on the data analysis that has been processed, it is concluded that the KKN Group 79 work program will conduct counseling by increasing natural potential through the tourism sector, namely Luweng Sampang which is a tourist attraction in the form of waterfalls and increasing the potential for biogas through the livestock sector, namely processing goat waste into organic fertilizer to be produced which is then marketed to improve the economy of the people of Sampang Village, Gedangsari District, Gunung Kidul Regency.